Studi Kualitatif Persepsi Mahasiswa terhadap Peluang Industri Kopi Nasional Pasca Pandemi - Muhammad Setiawan Kusmulyono; Sri Widya Wijanarti; Harindra Damarsatya Prashasta (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Coffee is an internationally traded commodity that has been affected by both the pandemic and the global economic downturn. However, the success of a national coffee company that was valued at one billion dollars demonstrates that coffee demand has a lot of potential. This study will use a qualitative research approach to find out what students think about the potential for the national coffee business following the pandemic. This student is a one-of-a-kind resource who has completed Prasetiya Mulya University's Coffee Business and Management Course. According to the findings of this study's thematic analysis, after the pandemic, perceptions of coffee trends and business prospects are projected to rise, but this will result in more intense competition among business actors. Coffee consumption habits, on the other hand, are predicted to be maintained during the pandemic, from buying liters of coffee to ordering via apps to the practice of brewing coffee at home.